Borneo excursion / Nur Atiqah Husaini and Shahril Anwar Mahmud - Husaini, Nur Atiqah; Mahmud, Shahril Anwar (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The theme for the project was BORNEO EXCURSION: Cataloging art and culture. Borneo is steeped in cultural diversity and traditions from the past up till this very day. Inspired by the various boom of cultural and art festivals in Sarawak, the students explored the rich native arts and crafts that makes up the culture and tradition of the people. The objective of the brief is to introduce students on basic vocabulary of design language and expose students on how to appreciate original ideas of design through analyzing ideas and concepts. The second project aims to introduce students to various art movements and the application of techniques in presentation as well as relating the application of the elements and principles of design in the work of architecture. The tasks introduced the students to development of 2D and 2.4D pattern and texture.